2022
DOI: 10.1021/acsomega.2c05299
|View full text |Cite
|
Sign up to set email alerts
|

Photo-On-Demand Synthesis of α-Amino Acid N-Carboxyanhydrides with Chloroform

Abstract: Amino acid N-carboxyanhydrides (NCAs) are conventionally synthesized from α-amino acids and phosgene. The present study reports in situ photo-on-demand phosgenation reactions of amino acids with CHCl3 for synthesizing NCAs. A series of NCAs were obtained on a gram scale upon photo-irradiation of a mixture solution of CHCl3 and CH3CN containing an amino acid at 60–70 °C under O2 bubbling. This method presents a safe and convenient reaction controlled by light without special apparatuses and reagents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…To ensure safe use of this reaction, we then developed "in situ" photo-ondemand phosgenation reactions, which required the design and construction of batch and flow reaction systems [25][26][27][28][29][30][31][32][33][34]. We have successfully applied this photo-ondemand phosgenation reaction on a practical scale for most common phosgenation reactions, such as the syntheses of chloroformates [25,26], carbonate esters [28,29], PCs [28], isocyanates [30], Vilsmeier reagents [27], acyl chlorides [25], and α-amino acid N-carboxyanhydrides (NCAs) [32] (Fig. 3).…”
Section: Introductionmentioning
confidence: 99%
“…To ensure safe use of this reaction, we then developed "in situ" photo-ondemand phosgenation reactions, which required the design and construction of batch and flow reaction systems [25][26][27][28][29][30][31][32][33][34]. We have successfully applied this photo-ondemand phosgenation reaction on a practical scale for most common phosgenation reactions, such as the syntheses of chloroformates [25,26], carbonate esters [28,29], PCs [28], isocyanates [30], Vilsmeier reagents [27], acyl chlorides [25], and α-amino acid N-carboxyanhydrides (NCAs) [32] (Fig. 3).…”
Section: Introductionmentioning
confidence: 99%
“…The reaction occurred efficiently in a short time upon irradiation of CHCl 3 under O 2 bubbling using UV-C light from a low-pressure mercury lamp (LPML). We then developed photo-on-demand in situ phosgenation reactions for synthesizing a variety of organic chemicals and polymers with CHCl 3 solutions containing both a substrate and an organic base [Scheme , reaction (c)]. Although alcohols such as EtOH serve to stabilize CHCl 3 , and the organic bases and solvents absorb UV-C light, , the phosgenation products were obtained in high yields through in situ reactions of the substrates and COCl 2 generated from CHCl 3 . These results indicated that the photochemical oxidation of CHCl 3 occurred not only in the liquid phase but also in the gas phase.…”
Section: Introductionmentioning
confidence: 99%
“…95 More recently, they have also reported CHCl 3 oxygenation under visible-light irradiation using trace amounts of Cl 2 as an initiator. 96,97 In addition, our research group has developed a CHCl 3 oxygenation reaction via the photoactivation of ClO 2 (Scheme 20). 98 Carbamoyl chlorides were synthesised from a wide substrate range by the phosgenation of amines under visible-light irradiation (l 4 400 nm) as ClO 2 exhibits a strong absorption band in the visible-light region (Fig.…”
mentioning
confidence: 99%